Promoción en posiciones de trabajo y prevención de malas posturas en la práctica odontológica en los estudiantes de la clínica de la universidad Antonio Nariño sede Cúcuta (2021)
For dentists, positions are determined by design, workplace structure and relationship to unilateral positions or body angles. The assessment of knowledge in Ergonomics was carried out according to the Likert scale, where a result was obtained Good 13.75% (n:11 students), Regular 68.75% (n:55 students) and Bad 17.5% (n:14 student). The Ergonomics Manual in Dentistry was designed, and the learning instruction in Ergonomics and the manual were socialized to the study participants.